Health and production of feedlot cattle following supplementation with urea–molasses in starter pens. Issue 5 (May 2014) - Croft, IA; Clayton, EH; Cusack, PMV
<x xml:space="preserve">Abstract</x> Objective To determine the effect of providing a urea–molasses supplement to cattle during feedlot introduction on average daily gain, carcase weight and bovine respiratory disease (BRD) morbidity and mortality. Methods Commercial mixed sex, mixed breed cattle (387.4 ± 0.2 kg) were systematically allocated to receive 2.1 L/animal of urea–molasses during feedlot introduction (n = 2307) or remain untreated (n = 2336). Cattle remained in the feedlot for an average of 40 days until reaching slaughter weight. Body weight data was collected prior to feedlot induction and all cases of BRD morbidity and mortality were determined during feeding. Hot standard carcase weight and P8 fat thickness were determined at slaughter. Results Average daily gain (1.94 ± 0.06 vs 1.93 ± 0.06, P = 0.650), BRD incidence (6.46% vs 5.53%, P = 0.183) and BRD mortality (0.17% vs 0.21%, P = 0.752) did not differ between supplemented and unsupplemented cattle. The BRD incidence was higher (P = 0.017) when cattle without permanent incisors were supplemented with urea–molasses (7.26%) compared with unsupplemented cattle (5.26%), and was also higher in steers compared with heifers (12.7% vs 7.8%, P < 0.001) and higher in cattle purchased from saleyards compared with cattle purchased off paddocks (12.4% vs 5.7%, P < 0.001). Conclusions Health and production were not significantly improved following supplementation of cattle with urea–molasses during feedlot introduction. BRD incidence was, however, significantly related to cattle sex and source. Further research is required to understand the relationship between feeding high non‐protein nitrogen sources and BRD morbidity in young cattle.